Sex differences in the association between blood pressure and atrial fibrillation: A case-control study - Zhao, Xiexiong; Feng, Qilun; Wahid, Abdul; Wang, Xiaoyan; Wen, Juan; Jiang, Weihong; Tang, Xiaohong (Frontiers in Cardiovascular Medicine, 2022)
Background: To examine the association of hypertension (HBP) and its control with atrial fibrillation (AF) and how patient sex affect this association. Methods: A case control study of patients admitted to our hospital from 2015 to 2019 was conducted. Patients were divided into subgroups according to their blood pressure (BP) levels and control status, in which odd ratios (OR) by sex for AF were estimated using a logistic regression model and restrictive cubic splines before and after propensity score matching. Results: A total of 3,212 patients with AF and 8,307 without AF were investigated. Compared to patients with normal BP, patients with HBP had more AF [OR = 1.75 (1.52-2.02), OR = 2.66 (2.24-3.15), and OR = 4.30 (3.40-5.44) in patients with grade 1, 2, and 3 HBP, respectively]. In HBP patients with grade 3, the OR of AF was much higher in women than in men (OR = 7.15, 95% CI: 4.43-11.50 vs. OR = 2.48, 95% CI: 1.66-3.72). BP over 133.1/79.9 mmHg in men or 127.1/75.1 mmHg in women was positively associated with AF. In patients with HBP, uncontrolled BP was more associated with AF (OR = 3.00, 95% CI: 2.53-3.56), especially in women (OR = 3.09, 95% CI: 2.27-4.19). BP and prevalence of AF correlated with each other positively in patients admitted to a cardiology ward. Lowering BP to 145.1/85.8 mmHg in men or 140.5/82.5 mmHg in women led to less AF. Conclusions: There is more significant relationship between HBP and AF in female patients. A lower and individualized BP target may be formulated to prevent AF in women.